Relationship between the level and the action period of fiber in diets to laying hens - João Paulo Ferreira Rufino; Frank George Guimarães Cruz; Ronner Joaquim Mendonça Brasil; Pedro Alves de Oliveira Filho; Ramon Duque Melo; Julmar da Costa Feijó (Acta Scientiarum. Animal Sciences, 2020)
The aim of the present study was to evaluate the relationship between the level of fiber and its action period in diets to laying hens on performance and egg quality. 180 Hisex white hens (65 weeks-old) were randomly allocated to 3 groups of 60 birds each, comprising 10 replicates of six birds per treatment. The experimental design was factorial scheme considering three levels of fiber (2.50, 4.87 and 7.24%) in birds’ diets, and three action periods of this fiber (short - 21 days, medium - 56 days, and long - 105 days) in the feed. The estimates of treatments were firstly subjected to ANOVA and a subsequent Tukey test at 5%. Birds fed diets with moderate levels of fiber (4.87%) presented better (p < 0.05) performance. High levels of fiber caused a significant reduction in performance. Birds fed diets with low and moderate levels of fiber produced eggs with better (p < 0.05) quality. High levels of fiber caused a significant reduction in egg quality. The exposure of birds to diets with fiber for long-term caused a negative effect (p < 0.05) on performance, egg weight and percentage of its main structures, albumen height, yolk height, eggshell thickness, and the specific gravity.